Penyuluhan dan Pendampingan Ibu Hamil dan Ibu Postpartum untuk Keberlangsungan Menyusui dengan Program WeChat - Novita, Regina Vidya Trias; Isnawati, Yunita Dwi; Marni, Nursanty Wardoyo; Dessy, Eva Milla; Wiliastari, Winwin; Sunarti, Sunarti; Permana, Leonal Yudha (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
The actually, many mothers experience difficulties and face several problems during the breastfeeding process after discharge. Mothers when control at hospital asked their problems. The aim are to help mothers to solved their problems after discharge with We Chat through giving information about breastfeeding, which is a means of providing nutrition for newborns. And companion mother four weeks. One way to help the problems of mothers in the breastfeeding process is to provide knowledge related to breastfeeding both for pregnant women at the end of their pregnancy with gestational age above 35 weeks and post-natal mothers as preparation and assistance in breastfeeding which is facilitated by health workers. The output target of this activity is to increase the knowledge and behavior of breastfeeding directly and confidently. The results of the PKM are attended by 60 participants, who were willing to assist 28 pregnant and lactating women. There are 12 pregnant women and the rest are breastfeeding. The level of knowledge of respondents is only 30% who know the signs of a baby being satisfied with breastfeeding, taking turns breastfeeding, and the importance of breastfeeding at night. After being given knowledge and assistance, respondents experienced an increase of almost 70%. The average participant has low self-confidence at the beginning, after mentoring it can reach almost 90%. The failure factor occurs because they have used a pacifier to provide nutrition, so direct breastfeeding takes a long time. This WeChat program is carried out for one month in the Tangerang and Cibubur areas. Breastfeeding support through the WeChat program uses whatsup media for tele counseling, namely one by one in the breastfeeding process from the beginning to practicing independently with confidence in breastfeeding.